2008
DOI: 10.1158/1541-7786.mcr-08-0109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exogenous Tissue Factor on Estrogen Receptorα Expression in Breast Cancer Cells: Involvement of β1-Integrin, PAR2, and Mitogen-Activated Protein Kinase Activation

Abstract: Increased expression of tissue factor (TF) has been associated with invasive forms of breast cancer. Conversely, the loss of estrogen receptor A (ERA) is associated with increased cell invasiveness. We have examined the influence of exogenous truncated recombinant TF (rTF) on ERA expression and cell invasiveness and investigated the mechanism of rTF signaling. The influence of rTF on ERA expression in MCF-7 and T47D cell lines was investigated using reverse transcription-PCR and ELISA. Cell invasion was measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…The disruption of alveolar epithelial cell attachments to the basement membrane seen in microscopy of TF ΔLEpi mice raises the possibility that additional noncoagulant mechanisms are involved in permeability maintenance. For example, TF is known to interact with b1-integrin and actin during cancer metastasis (47,48). Whether TF interacts with b1-integrin or other cytoskeletal structures in lung epithelial cells is unknown, and is the focus of ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of alveolar epithelial cell attachments to the basement membrane seen in microscopy of TF ΔLEpi mice raises the possibility that additional noncoagulant mechanisms are involved in permeability maintenance. For example, TF is known to interact with b1-integrin and actin during cancer metastasis (47,48). Whether TF interacts with b1-integrin or other cytoskeletal structures in lung epithelial cells is unknown, and is the focus of ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…11 We have previously demonstrated the interaction of lipidated recombinant TF with the ␤1-integrin subunit and shown that this was independent of FVIIa. 10 However, the mechanism by which TF interacts with integrins remains unclear.…”
mentioning
confidence: 99%
“…Exogenously synthesized TF in patients may affect a number of breast cancer cell characteristics. It was revealed that a paracrine effect of TF can influence the growth and metastasis of breast cancer cells [79] . Treatment of cells with recombinant TF, mimicking stromal-derived TF (Figure 3), enhances the invasive and proliferative properties of these cells.…”
Section: Exogenous Tfmentioning
confidence: 99%
“…Treatment of cells with recombinant TF, mimicking stromal-derived TF (Figure 3), enhances the invasive and proliferative properties of these cells. This occurs via activation of β1-integrins and/or PAR2-dependent signals, followed by inactivation of transcription of the estrogen receptor (ER) gene [79] (Figure 3). The involvement of integrins in TF-driven phenotype expressions of breast cancer cells is similar to the findings that association of TF integrated into plasma membrane of keratinocytes and breast cancer cells bind integrins and may support growth of breast tumor [30] .…”
Section: Exogenous Tfmentioning
confidence: 99%